Juvenile hyaline fibromatosis - Vikram Karande; Neelam Noel Andrade (Wolters Kluwer Medknow Publications, 2018)
Syndromes, especially if they occur early in the growth phase can be very debilitating and cause severe restriction of function. Juvenile hyaline fibromatosis is one such disorder. Our case report presents a girl child who was diagnosed with this debilitating condition. The case presented with both - general characteristic features of this condition such as subcutaneous nodules and flexion deformity of the joints, as well as local manifestation in the form of gingival overgrowth. Thorough clinical and radiological investigations were done to arrive at the diagnosis which was supported conclusively with histopathology of the biopsied gingival lesions. A combination of both medicinal as well as surgical therapeutic modalities was used. This case report is an effort to comprehensively document the etiology, clinical features, and prognosis of this syndrome. There being no permanent cure for the condition, the case report highlights the unique management protocol employed by us in the form of intralesional steroid therapy with endocrine consultation and the local surgical gingival excision carried out in an attempt to optimize the quality of life for our patient.